Physical therapists’ knowledge, attitudes, and practices in cardiovascular assessment: a brief review - Sheetal; Sikka, Gitanjali (International Journal of Research in Medical Sciences, 2024)
This comprehensive review paper investigates current practices, attitudes, and knowledge related to cardiovascular risk and blood pressure monitoring in physical therapy settings. A thorough search strategy was employed for the review, covering key databases like PubMed and Google Scholar up to march 2024. This approach ensured comprehensive retrieval of studies that cover a range of topics related to cardiovascular risk assessment, blood pressure management, and the knowledge and practices of physical therapists in these areas. The study concludes that there is a notable gap in the knowledge and practice of blood pressure (BP) and heart rate (HR) assessment among physical therapists. There is need to address knowledge deficits of physical therapists regarding screening of cardiovascular parameters. Also, revision of clinical policies could enhance the implementation of assessment of these parameters in regular clinical practises and ultimately improve patient outcomes.